Management of hypertension in the elderly patient - Gordon Stewart Stokes (Dove Medical Press, 2009)
Gordon Stewart Stokes1,21Northern Clinical School, University of Sydney, Sydney, New South Wales, Australia; 2Department of Cardiology, Royal North Shore Hospital, St. Leonards, New South Wales, AustraliaAbstract: Hypertension in the elderly is associated with increased occurrence rates of sodium sensitivity, isolated systolic hypertension, and ‘white coat effect’. Arterial stiffness and endothelial dysfunction also increase with age. These factors should be considered in selecting antihypertensive therapy. The prime objective of this therapy is to prevent stroke. The findings of controlled trials show that there should be no cut-off age for treatment. A holistic program for controlling cardiovascular risks should be fully discussed with the patient, including evaluation to exclude underlying causes of secondary hypertension, and implementation of lifestyle measures. The choice of antihypertensive drug therapy is influenced by concomitant disease and previous medication history, but will typically include a thiazide diuretic as the first-line agent; to this will be added an angiotensin inhibitor and/or a calcium channel blocker. Beta blockers are not generally recommended, in part because they do not combat the effects of increased arterial stiffness. The hypertension–hypotension syndrome requires case-specific management. Drug-resistant hypertension is important to differentiate from faulty compliance with medication. Patients resistant to third-line drug therapy may benefit from treatment with extended-release isosorbide mononitrate. A trial of spironolactone may also be worthwhile.Keywords: hypertension, elderly, antihypertensive treatment, patient management